Unraveling the Simultaneous Enhancement of Selectivity and Durability on Single‐Crystalline Gold Particles for Electrochemical CO2 Reduction. Issue 20 (2nd May 2022) - Lim, Yun Ji; Seo, Dongho; Abbas, Syed Asad; Jung, Haeun; Ma, Ahyeon; Lee, Kug‐Seung; Lee, Gaehang; Lee, Hosik; Nam, Ki Min
Abstract: Electrochemical carbon dioxide reduction is a mild and eco‐friendly approach for CO2 mitigation and producing value‐added products. For selective electrochemical CO2 reduction, single‐crystalline Au particles (octahedron, truncated‐octahedron, and sphere) are synthesized by consecutive growth and chemical etching using a polydiallyldimethylammonium chloride (polyDDA) surfactant, and are surface‐functionalized. Monodisperse, single‐crystalline Au nanoparticles provide an ideal platform for evaluating the Au surface as a CO2 reduction catalyst. The polyDDA‐Au cathode affords high catalytic activity for CO production, with >90% Faradaic efficiency over a wide potential range between −0.4 and −1.0 V versus RHE, along with high durability owing to the consecutive interaction between dimethylammonium and chloride on the Au surface. The influence of polyDDA on the Au particles, and the origins of the enhanced selectivity and stability are fully investigated using theoretical studies. Chemically adsorbed polyDDA is consecutively affected the initial adsorption of CO2 and the stability of the *CO2, *COOH, and *CO intermediates during continuous CO2 reduction reaction. The polyDDA functionalization is extended to improving the CO Faradaic efficiency of other metal catalysts such as Ag and Zn, indicating its broad applicability for CO2 reduction. Abstract : Single‐crystalline Au provides an ideal platform for evaluating the Au surface as a CO2 reduction catalyst. The polyDDA functionalized Au electrode shows high catalytic activity and durability for CO production. Interestingly, polyDDA functionalization can be widely applied to other metal catalysts such as Ag and Zn. This functionalization affords broad applicability for utilizing metal catalysts for efficient CO2 reduction reactions.